Sustentabilidade empresarial: o caso Dow Jones Sutainability Index - Zago, Ana Paula Pinheiro (2007)
The choice made by a company to be part of DJSI generates a series of expectations concerning the potential benefits of it. It is expected that the investment regarding sustainable development and the subsequent inclusion of the enterprise in this select group, beyond facilitating the access to financial resources and improving its image, will bring economic and strategic benefits that will influence the firm s valuation. However, the relationship between environmental and social performance and financial performance is extremely complex. On one hand, some authors affirm that the sustainability investment provides improvements in the financial performance. On the other hand, others argue that the benefits are smaller than the investments. Bearing in mind this controversy, this study aims to investigate if the inclusion of given company in the DJSI, which is understood as a proxy of high environmental and social performance, will imply a higher financial return. The study of event is used as methodology to investigate the existence of abnormal returns when the information about the inclusion of the company in the DJSI is released. In other words, the study tests the hypothesis that this event will deliver positive impacts. The sample consists of enterprises that are part of DJSI Edition 2005/2006 and have their shares trade at the New York Stock Exchange (NYSE). The financial data, before and after the event, was obtained from Yahoo financial website, while the date of inclusion of the companies in the DJSI was supplied from NYSE. In order to calculate the abnormal return, the method return adjusted to the risk and the market was used. The main outcomes of this dissertation indicate a null effect, nor confirming the hypothesis of higher returns due to inclusion in the DJSI, neither indicating a reduction of financial performance.